Given (96)^{3}

96 can be expressed as the sum or difference of two numbers and then binomial theorem can be applied.

The given question can be written as 96 = 100 – 4

(96)^{3} = (100 – 4)^{3}

= ^{3}C_{0} (100)^{3} – ^{3}C_{1} (100)^{2} (4) – ^{3}C_{2} (100) (4)^{2}– ^{3}C_{3} (4)^{3}

= (100)^{3} – 3 (100)^{2} (4) + 3 (100) (4)^{2} – (4)^{3}

= 1000000 – 120000 + 4800 – 64

= 884736

Answered by Abhisek | 1 year agoFind the term independent of x in the expansion of \( (\dfrac{3}{2x^2} – \dfrac{1}{3x})^9\)

Find the middle term in the expansion of \((x-\dfrac{ 1}{x})^{2n+1}\)

Find the middle term in the expansion of (1 + 3x + 3x^{2} + x^{3})^{2n}

Find the middle term in the expansion of (1 – 2x + x^{2})^{n}

Find the middle term in the expansion of \( (\dfrac{x}{a} – \dfrac{a}{x})^{10}\)